STRATEGIC HUMAN RESOURCE MANAGEMENT AND FIRM PERFORMANCE IN JORDAN LISTED FIRMS - Al- Raggad, Mohammad Abdelkareem (European Scientific Journal, ESJ, 2014)
The objectives of this research paper were to investigate whether competency, education,experience, age and hierarchical level of human resource manager of the listed firmsrelate to the practice of SHRM of those firms; and to investigate whether these factorshave a significant joint impact on the practice of SHRM of listed companies in Jordan. A research framework consisting of five independent variables and one dependentvariable was developed and six hypotheses were formulated using deductive approach. The study was conducted relating to some listed firms numbering 200. Purposeof the study, type of investigation, extent of researcher interference with the study, studysetting, unit of analysis and time horizon were hypotheses testing, noncausal, minimal,noncontrived, individual and crosssectional respectively. Measures of the study hadpossessed sufficient validity and reliability. The structured questionnaire wasadministered to cover all the firms and head of human resource department worked asthe respondents on behalf of the firms. 161 human resource heads responded making aresponse rate of 80.5 per cent. Data exploration ensured the normality and linearityassumptions being not violated. The results of the study showed significant and positiverelationships between the independent variables, i.e., competence, education, experience,and hierarchical level of human resource managers and the dependent variable, i.e.,practice of SHRM. However, no significant relationship was found between age of humanresource manager and practice of SHRM. Multivariate analysis revealed that combinedinfluence of competency, education, experience, age, and hierarchical level of humanresource manager on the perceived practice of SHRM within a firm was significant.Findings of the study will be important on practical grounds. Important implications ofthe findings of the study are that a firm should hire and retain a person as the Head ofHRM who should possess a high competence of HRM, higher formal education of HRM,and more experience in HRM in order to establish a serious practice of JHRM, and alsothe Head of HRM is to be appointed as a member of the Top Management of the firm.